Kepemimpinan Berbasis Nilai Dan Etika, Bagi Anak Dan Remaja Di Panti Asuhan Pelangi III, Kota Sorong, Papua Barat Daya - Leuwol, Natasya Virginia; Gasperzs , Sherly; Wonmaly , Windy; Indonesia, Mahasiswa Prodi Bahasa & Sastra (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Basically, every child already has the potential to become a leader. Therefore, leadership skills in children must be applied from an early age as a solid foundation to realize their dreams and goals in life. The spirit of leadership can basically train a sense of responsibility, discipline, and perseverance that are beneficial for the future of children. According to experts, the age of children is the right time to teach the importance of having a leadership attitude in themselves, because the age of children is the initial phase of the character formation process. So do not be surprised if we see in schools the subject matter and learning methods that are applied emphasize more on the formation of children's character. This study aims to cultivate children's values-based leadership and ethic. This type of service is descriptive qualitative. There are many ways that can be done by the younger generation in developing a leadership spirit, one of which is through compromise and tolerance with others. This is important today because of the development of globalization, the ways of thinking, behavior, attitudes, and lifestyles are also increasingly worrying. Therefore, children's values-based leadership and ethic can be used as references on how to develop leadership attitudes in the younger generation so that in the future they will become a generation of bright leaders.